PENGARUH HARGA TERJANGKAU TERHADAP LOYALITAS PELANGGAN PADA MAHASISWA FAKULTAS EKONOMI DI KANTIN FIP UNIMED - Sitanggang , Karolin Gabrela; Munthe, Paula; Putri, Maysri Handayani; Tumangger, Salamah; Syahputra, Irfandi; Wardani, Nurul (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
Consumer loyalty is a crucial asset for business sustainability, especially in university environments where students with limited purchasing power often prioritize affordable pricing. This study aims to analyze the impact of affordable pricing on consumer loyalty among Economics Faculty students at FIP UNIMED Canteen. The research employs a quantitative approach with simple linear regression, involving 70 respondents selected through purposive sampling. Primary data was collected via a Likert scale 1-5 questionnaire, analyzed using SPSS for validity, reliability, classical assumption tests, and regression. Results indicate that affordable pricing has a significant positive effect on consumer loyalty (t-calculated = 4.637 > t-table = 1.98, p < 0.05), with a coefficient of determination of 24.0%. The conclusion states that affordable pricing enhances loyalty through repeat purchases and recommendations, providing insights for canteen managers to develop effective pricing strategies.